THE GUT–BRAIN AXIS IN NEURODEGENERATIVE DISEASES: LINKING MICROBIOTA DYSBIOSIS, BARRIER DYSFUNCTION, AND NEUROINFLAMMATION - Lina Eka Dewi; Elfi Yulfientir; Arief Rinaldy; Nilas Warlem (Yayasan Nusantara Hasana Berdikari, 2026)
Neurodegenerative diseases (NDDs), including Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, and amyotrophic lateral sclerosis, are characterized by progressive neuronal dysfunction and loss. Neuroinflammation, immune dysregulation, oxidative stress, and mitochondrial dysfunction are increasingly recognized as interconnected mechanisms in disease progression. The gut–brain axis provides a bidirectional link between the gastrointestinal tract and central nervous system through neural, immune, endocrine, and metabolic pathways. Gut microbiota dysbiosis may contribute to neurodegeneration through impaired intestinal barrier integrity, altered microbial metabolites, systemic inflammation, and blood–brain barrier dysfunction. Changes in short-chain fatty acids, tryptophan-derived metabolites, bile acids, and microbial products such as lipopolysaccharide may modulate immune and glial signaling, including TLR4/NF-κB and NLRP3 pathways. Evidence is particularly prominent in Alzheimer’s and Parkinson’s diseases, although microbial alterations remain heterogeneous across studies. The gut–brain axis represents a potentially modifiable interface linking microbial dysbiosis and neuroinflammation. Microbiome-targeted interventions show promising but inconsistent results. Further integration of microbiomics, metabolomics, immunophenotyping, and longitudinal clinical data is needed to establish causality and advance precision strategies for neurodegenerative diseases.